Obtenção, caracterização físico-química e biocompatibilidade da hidroxiapatita derivada da corvina (micropogonias furnieri) - Yamamura, Hirochi [UNIFESP] (2016)
The main objective of the present work was to develop a method of obtaining hydroxyapatite from the bones by-product of whitemouth croaker fish (Micropogonias furnieri) disposed as a waste at the local Fish Market. The new method was developed by proposing a treatment with sodium hydroxide, hydrogen peroxide and subsequent calcination at 800 °C. The chemical composition and the crystalline structure was controlled by physical-chemical and instrumental analysis as X-ray diffraction, ICP spectrometry, infrared spectrometry, ion chromatography and scanning electron microscopy (SEM). The results revealed that the structure of the newly obtained hydroxyapatite (HAP-T) remained after calcination, after comparison with references data. In vivo biocompatibility tests using experimental models such as implantation in the subcutaneous, cyto- and genotoxicity in rodents were made in this setting. A total of 12 male Wistar rats were submitted to implantation of a fragment were evaluated to cyto- and genotoxicity in multiple organs such as: liver, kidney and lung by microscopic analysis and comet assay. The results demonstrated that hydroxyapatite (HAP-T) induced inflammatory process in the connective tissue after 7 days post-implantation. Resorption of biomaterial as well as decrease of inflammatory process were detected after 14 and 30 days. Lack of cyto- and genotoxicity were detected after 30 days postimplantation for all organs evaluated. The physico-chemical, instrumental, chemical analysis and in vivo biocompatibility, cyto- and genotoxicity tests demonstrated that the proposed method for extraction of Hydroxyapatite (HAP-T) from by-products of whitemouth croaker fish (Micropogonias furnieri) bone was feasible and the hydroxyapatite HAP-T was biocompatible and safety by cyto- and genotoxicity in vivo tests.